2017
DOI: 10.1111/1471-0307.12462
|View full text |Cite
|
Sign up to set email alerts
|

Differences in bioactive protein and vitamin status of milk from certified organic and conventional farms

Abstract: The aim of the study was to determine differences in the status of selected bioactive whey proteins and lipophilic vitamins in milk obtained from certified organic farms as compared to conventional farms (using traditional and intensive production systems). Significant relationships were noted with regard to production system and individual bioactive milk compounds, that is β‐lactoglobulin, lactoferrin, lysozyme, vitamins A, D3 and E, and β‐carotene (P = 0.001) and bovine serum albumin (BSA) (P = 0.016). Milk … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
52
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 27 publications
(60 citation statements)
references
References 32 publications
8
52
0
Order By: Relevance
“…The seasonal differences in the content of α-LA, β-LG and lactoferrin in milk were also obsereved. The highest level of these proteins (with regard to the feeding system, excluding group 3) was found in the summer, which corresponded well to the results of other studies (Wedholm et al, 2006;Litwińczuk et al, 2011;Brodziak et al, 2018). A larger share of industrial fodder in ration negatively affected the content of lysozyme in milk (r=-0.26 -summer; r=-0.28 -winter).…”
Section: Resultssupporting
confidence: 89%
See 2 more Smart Citations
“…The seasonal differences in the content of α-LA, β-LG and lactoferrin in milk were also obsereved. The highest level of these proteins (with regard to the feeding system, excluding group 3) was found in the summer, which corresponded well to the results of other studies (Wedholm et al, 2006;Litwińczuk et al, 2011;Brodziak et al, 2018). A larger share of industrial fodder in ration negatively affected the content of lysozyme in milk (r=-0.26 -summer; r=-0.28 -winter).…”
Section: Resultssupporting
confidence: 89%
“…Moreover, the share of industrial fodder and silage in the ration affected the growth of this protein fraction in milk. Similar tendencies were reported by Brodziak et al (2012;2018) and Mackle et al (1999). Mackle et al (1999), who showed that energy absorbed in the ration might affect the concentration of whey proteins in milk of cows, also including the serum proteins.…”
Section: Resultssupporting
confidence: 86%
See 1 more Smart Citation
“…Conversely, other studies suggest due to the content of bioactive compounds, aroma and flavour characteristics from high biodiversity organic pastures with numerous species of grasses, legumes and herbs, organic dairy products have special health benefits (Bergamo, 2003;Brodziak et al, 2018;Ellis et al, 2007;Kuczyńska et al, 2012;Popović-Vranješ et al, 2017).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Milk and dairy products are an important source of health-promoting substances in the human diet, including minerals and fat-soluble vitamins [ 1 , 2 , 3 , 4 , 5 ]. Vitamins are an important group of organic substances with high biological activity, essential for the growth and functioning of the body.…”
Section: Introductionmentioning
confidence: 99%